Bagasse ash - Payá, Jordi; Monzó, José; Borrachero, María V.; Tashima, Mauro M. [UNESP]; Soriano, Lourdes (Elsevier, 2018)
Sugarcane (Saccharum officinarum) is the largest crop by production quantity in the world. A large amount of wet bagasse is yielded and the management of this residue is of great importance from an environmental point of view. The combustion of this bagasse is one of the most common practices, resulting in the production of an additional residue, the sugarcane bagasse ash (SCBA). Chemical and mineralogical composition of SCBA makes it a potential supplementary material in Portland cement blends and also in geopolymeric binders. Fineness, crystallinity, and the presence of unburned particles are crucial for the development of pozzolanic reactivity and for having good mechanical performance. Durability of SCBA-based mortar and concrete is appropriate, and in many cases 20% replacement of cement can be carried out without significant performance loss. Also, SCBA and sugarcane straw ash are good candidates for preparing geopolymeric binary systems. A reduction of CO2 emissions has been proposed with the use of these residues.
Keywords: Bagasse residues; Biomass ash; CO2 emission saving; Concrete; Durability; Fineness; Geopolymer; Pozzolanic reactivity; Strength